STUDY OF THE CLINICAL COURSE, CHARACTERISTICS AND COMPLICATIONS OF PATIENTS INFECTED WITH THE COVID-19 VIRUS IN MALE AND FEMALE PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS - Abdullaev J.U; Mirakhmedova H.T (Scholar Express Journals, 2023)
In article is given analyses of clinical options, course and prognosis of systemic covid 19 lupus erythematosus in men. Systemic lupuserythematosus (SLE) severe chronic connective tissue disease of autoimmune nature. When the disease affects the skin, blood vessels,connective tissue all internal organs. SLE is commonly seen in young (mostly girls and women) who are at risk. The Defeat of theinternal organs has a special place in SLE.
Keywords: systemic lupus erythematosus; clinical variants; diagnostics; prognosis